2012
DOI: 10.1029/2011gl050399
|View full text |Cite
|
Sign up to set email alerts
|

Normal‐faulting earthquakes beneath the outer slope of the Japan Trench after the 2011 Tohoku earthquake: Implications for the stress regime in the incoming Pacific plate

Abstract: After the 2011 Mw 9.1 Tohoku earthquake, numerous intraplate earthquakes occurred beneath the outer slope of the Japan Trench. Based on ocean bottom seismograph observations, these earthquakes occurred in the oceanic crust and uppermost mantle of the Pacific plate at depths shallower than about 40 km and had normal‐faulting focal mechanisms at all depths. Before the 2011 earthquake, normal‐faulting earthquakes beneath the outer trench slope occurred only at depths shallower than 20 km, whereas those at depths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
60
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 20 publications
11
60
1
Order By: Relevance
“…This result is in stark contrast with a recent model of the Earth's water budget that uses slab water flux models, volcanic outputs, and estimates of global sealevel during the Phanerozoic to constrain the maximum amount of water that is brought into the subduction zone (Parai and Mukhopadhyay, 2012). Parai and Mukhopadhyay (2012) suggest that even the conservative estimates of Van Keken et al (2011) overestimate the amount of water input into subduction zones globally. Our results presented in this paper have an even larger discrepancy with the estimates of Parai and Mukhopadhyay (2012).…”
Section: Implications To Global Water Budgetscontrasting
confidence: 65%
See 1 more Smart Citation
“…This result is in stark contrast with a recent model of the Earth's water budget that uses slab water flux models, volcanic outputs, and estimates of global sealevel during the Phanerozoic to constrain the maximum amount of water that is brought into the subduction zone (Parai and Mukhopadhyay, 2012). Parai and Mukhopadhyay (2012) suggest that even the conservative estimates of Van Keken et al (2011) overestimate the amount of water input into subduction zones globally. Our results presented in this paper have an even larger discrepancy with the estimates of Parai and Mukhopadhyay (2012).…”
Section: Implications To Global Water Budgetscontrasting
confidence: 65%
“…Parai and Mukhopadhyay (2012) suggest that even the conservative estimates of Van Keken et al (2011) overestimate the amount of water input into subduction zones globally. Our results presented in this paper have an even larger discrepancy with the estimates of Parai and Mukhopadhyay (2012).…”
Section: Implications To Global Water Budgetsmentioning
confidence: 99%
“…However, aftershocks of the 2011 Tohoku earthquake within the subducting oceanic plate had mostly normal fault type, or strike-slip type, mechanisms. Obana et al (2012) found that earthquakes beneath the seaward slope of the Japan Trench after the mainshock occurred under a tensional stress field in all depths and concluded that the stress regime in the deep part of the subducting oceanic plate in the seaward slope had changed from compression to tension after the mainshock. Our results indicate that the tension stress field extends to the oceanic plate below the landward slope of the Japan Trench.…”
Section: Resultsmentioning
confidence: 99%
“…When the bending-induced stress exceeds the yield strength of the lithosphere, pervasive faulting could occur trenchward of the outerrise region (e.g. Jones et al 1978;Masson 1991;Ranero et al 2003Ranero et al , 2005Obana et al 2012;Gou et al 2013;Naliboff et al 2013;Boston et al 2014;Craig et al 2014;Zhou et al 2015). Faulting could in turn cause a significant reduction in the effective elastic thickness of the subducting plate Bodine & Watts 1979;Watts 2001;Ranero et al 2005;Contreras-Reyes & Osses 2010;Zhang et al 2014;Hunter & Watts 2016).…”
Section: Introductionmentioning
confidence: 99%